Analysis of The Influence of School Internal Factors on The Quality of Islamic Education at SMAN 1 Gerung - Dhomroh, Siti; Sulhan, Ahmad; Hakim, Lukman (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to explain the impact of internal school factors on the quality of Islamic education at SMAN 1 Gerung. Using a quantitative approach with an analytical design, the study involved the principal and 36 teachers selected through random sampling. Data collection included observation and questionnaires based on indicators and sub-indicators of the variables. Data analysis through t-tests and F-tests revealed a significant value of 0.001, indicating a strong influence of internal factors on Islamic education quality. The results confirm the alternative hypothesis, suggesting a significant impact of internal school factors on the quality of Islamic education. These findings are expected to guide the development of programs to enhance Islamic education quality at SMAN 1 Gerung.